The Effect of Local Original Revenue, General Allocation Funds, and Special Allocation Funds on Economic Growth and Human Development Index with Capital Expenditure as Intervening Variable - Megawati*, Farah Tri; Hanifah, Imam Abu; Ismawati, Iis (Universitas Syiah Kuala, 2024)
The purpose of this study is to understand and analyze the effects of GDP, GDPU, and GDPK on GDP and the Index of Human Development with real money (BM) as intervening variables. The method used in this study is the structural equation model, or SEM, in conjunction with partial least squares, or PLS. The results of this study indicate that: Regional original income has a negative impact on economic growth; The General Allocation Fund has a negative impact on economic growth; The Special Allocation Fund has a negative impact on economic growth; Local original income has a positive impact on the Human Development Index; The General Allocation Fund has a negative impact; The Special Allocation Fund has a not-significantly-positive impact; Local original revenue has a positively significant positive impact on capital expenditure; The General Allocation Fund has a significant positive effect on Capital Expenditure; the Special Allocation Fund has a negative insignificant effect on Capital Expenditure; Capital Expenditure has a significant positive effect on Economic Growth; Capital Expenditure has a significant positive effect on the Human Development Index; Regional Original Income has a significant positive effect on Economic Growth through Capital Expenditure as an intervening variable; The General Allocation Fund has a positive and insignificant effect on Economic Growth through Capital Expenditure as an intervening variable; The Special Allocation Fund has a negative and insignificant effect on Economic Growth through Capital Expenditure as an intervening variable; Regional Original Income has a significant positive effect on the Human Growth Index through Capital Expenditure as an intervening variable; The General Allocation Fund has a positive and insignificant effect on the Human Growth Index through Capital Expenditure as an intervening variable; The Special Allocation Fund has a negative and insignificant effect on the Human Growth Index through Capital Expenditure as an intervening variable.